Dynamic distribution and correlation analysis of the angle kappa in myopia patients undergoing femtosecond-assisted laser in situ keratomileusis. Issue 24 (17th June 2022) - Deng, Wen-Qing; Fang, Yu-Hui; Lin, Shu-Hua; Li, Ying-Jun
Abstract: Purpose: To explore the offset distribution of pupillary centres, the offset between the pupil centre and the coaxially sighted corneal light reflex ( P-Dist ) and their correlation in femtosecond laser combined with excimer laser in situ keratomileusis. Methods: Randomly selected 194 patients (398 eyes) who underwent femtosecond-assisted laser in situ keratomileusis with preoperative use of WaveLight Allegro Topolyzer Corneal Topography (WaveLight Laser Technologies AG, Erlangen, Germany) to measure the pupil size and centre position. The P-Dist of the patients was recorded by the X and Y axis eyeball tracking adjustment program of the WaveLight Eagle Vision EX500 excimer laser system. Results: The P-Dist was 0.214 ± 0.092 mm in the right eyes and 0.228 ± 0.105 mm in the left eyes ( P  = .041). Under scotopic conditions, the pupil centre of left eye X -axis was −0.046 ± 0.091 mm, the right eye was −0.152 ± 0.084 mm, with significant differences ( P  = .015), and the Y -axis direction showed no significant changes ( P  = .062). The white to white was positively correlated with changes of pupil diameter (scotopic pupil diameter-photopic pupil diameter) ( r  = 0.270, P  < .001). The equivalent spherical mirror and measured centroid shift were negatively correlated ( r  = −0.214, P  = .002). Conclusion: The angle kappa of the right eye is smaller than that of the left eye and from scotopic to photopic condition, the pupil centroid shift of both eyes to the nasal inferior side. If the cornea is too large, the low illumination environment should be maintained during the operation to improve the efficiency of pupil matching.